Cultivation of Innovative Ability of College Physical Education Students Based on the Internet of Things Multimedia Environment - Bin Cai (International Transactions on Electrical Energy Systems)
Innovation is the source of social progress, and all walks of life need to cultivate innovative talents. Therefore, it is also very important to cultivate innovative ability in physical education students in colleges and universities. The purpose of this paper is to study the cultivation of students’ innovative ability of physical education majors in colleges and universities based on the multimedia environment of the Internet of things and to open up a new path for the cultivation of college students’ innovative ability. In this paper, a terminal collaborative indoor positioning algorithm based on RSSI fingerprint optimization was proposed to study the innovation ability of physical education students in colleges and universities. Through experimental analysis, college A was taken as the research object, and 1500 students were investigated. Innovation had a very important position in the hearts of 76.21% of students, and 3.83% of students believed that innovation was not important. In the minds of most people, innovation was still very important, which showed that schools still had a certain effect on the education of students’ innovative consciousness. The experimental results obtained showed that the Internet of things technology played an important role in the research on the innovation ability of students majoring in physical education in colleges and universities.